2013
DOI: 10.1021/ie400680t
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Blend Properties of Castor Biodiesel and Bioethanol

Abstract: Some important properties of biodiesel such as viscosity, melting point, thermal stability, and cetane index can be directly related to the chemical composition of the biomass source used. However, the viscosity of castor oil ethyl ester (COEE) is about four times greater than the biodiesel viscosity specification, and this fact restricts the uses of this biofuel. The main goal of this work is to investigate the physical–chemical properties of COEE in ethanol blends and present an option to decrease the castor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Castor bean biodiesel requires a negligible amount of catalyst to give a high biodiesel yield, reducing the production cost for large-scale operations [22,150]. Furthermore, castor bean biodiesel can be obtained at low temperatures [110,151]: for instance, Keera et al [143] produced castor bean biodiesel through alkaline transesterification, with biodiesel yield obtained at 30 • C similar to that obtained at 60 • C. It is highly soluble in alcohol, due to the presence of hydroxyl groups, with great advantage during transesterification [80,144,151,152]. A study by Bateni et al [110] demonstrated that the whole castor bean plant may be used in biodiesel production, with transesterification performed with ethanol obtained by saccharification and fermentation of plant residues; 1 kg of castor bean plant produced 149 g of biodiesel and 30.1 g of ethanol.…”
Section: Castor Bean Biodieselmentioning
confidence: 99%
See 1 more Smart Citation
“…Castor bean biodiesel requires a negligible amount of catalyst to give a high biodiesel yield, reducing the production cost for large-scale operations [22,150]. Furthermore, castor bean biodiesel can be obtained at low temperatures [110,151]: for instance, Keera et al [143] produced castor bean biodiesel through alkaline transesterification, with biodiesel yield obtained at 30 • C similar to that obtained at 60 • C. It is highly soluble in alcohol, due to the presence of hydroxyl groups, with great advantage during transesterification [80,144,151,152]. A study by Bateni et al [110] demonstrated that the whole castor bean plant may be used in biodiesel production, with transesterification performed with ethanol obtained by saccharification and fermentation of plant residues; 1 kg of castor bean plant produced 149 g of biodiesel and 30.1 g of ethanol.…”
Section: Castor Bean Biodieselmentioning
confidence: 99%
“…All the above-mentioned studies indicate that castor bean is a great feedstock for biodiesel production. Applying a mathematical experimental design and methodology, such as response surface methodology [151,154] or the Taguchi approach [155,156], can improve and optimize castor bean oil transesterification. New technological innovations, new diesel engines, and mathematical model applications could greatly increase castor bean biodiesel production and utilization.…”
Section: Castor Bean Biodieselmentioning
confidence: 99%
“…Identificação dos solventes empregado no processo de extração líquido-líquido e das respectivas purezas, marcas e massas molares. (Silva et al, 2006(Silva et al, , 2013.…”
Section: Extração Líquido-líquido Em Três Estágiosunclassified